PENYEBARAN KECEPATAN AIR PADA DIAMETER PIPA DN 250, DN 200 DAN DN 150 - naibaho, bonar sari monang; Halawa, Analiser (Jurnal Sains dan Teknologi ISTP, 2024)
Utilization of water is very necessary for household needs. These needs are distributed through pipe as media. The volume of water flowed depends on the amount needed. So proper distribution is needed. In the mining industry, water distribution is also needed. Especially in PIT. Distribution is aligned with the capacity (Sump) with rainfall and groundwater entering the mine. The choice of pipe also influences the amount of water distribution. Especially with the difference in height in the suction pipe and exhaust pipe. The author conducted research on 3 (three) pipe diameter sizes DN 250, DN 200 and DN 150. By observing these three types of sizes, the phenomenon of flow velocity in the pipe was obtained. The phenomenon that occurs is that the smaller the pipe size, the higher the speed of water flow in the pipe. Observations were also made in an area 0.006 m from the inner pipe. In this area, a balance of flow velocity is obtained in pipes with sizes DN 200 and DN 150. So that a speed selection of 0.48 m/s is obtained which corresponds to the DN 200 pipe.